2021
DOI: 10.37766/inplasy2021.1.0086
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Tai Chi on Balance Function and Exercise Capacity among Stroke Patients:A Meta-analysis

Abstract: Country(ies) involved: China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A meta-analysis of 19 RCTs suggested that tai chi may improve balance function and exercise capacity following stroke. 64 In a systematic review of eight studies, tai chi and yoga both showed promise for improving psychological stressors and quality of life among poststroke patients. 65 However, more rigorous and adequately powered RCTs are needed to better evaluate movement-based therapies in stroke.…”
Section: Evidence For Common Neurological Disordersmentioning
confidence: 99%
“…A meta-analysis of 19 RCTs suggested that tai chi may improve balance function and exercise capacity following stroke. 64 In a systematic review of eight studies, tai chi and yoga both showed promise for improving psychological stressors and quality of life among poststroke patients. 65 However, more rigorous and adequately powered RCTs are needed to better evaluate movement-based therapies in stroke.…”
Section: Evidence For Common Neurological Disordersmentioning
confidence: 99%
“…After practicing, the body feels relaxed and full of spirit [5]. Taijiquan exercise is not affected by time, space, environmental conditions, age, athletic ability, the intensity of the exercise, and the size of the exercise can be controlled by themselves, so taijiquan exercise is easy to promote popularization [6][7]. Taijiquan exercise at home or taijiquan rehearsal in the square can allow older people to exercise their bodies.…”
Section: Introductionmentioning
confidence: 99%